Law : a very short introduction - "Wacks, Raymond" (Oxford, 2015)
Law touches every aspect of our daily lives, and yet the main concepts, terms, and processes of the legal system remain obscure to many. This 'Very Short Introduction' provides a clear, jargon-free account of modern legal systems, explaining how the law works both in the Western tradition and around the world.
Keywords: Law